Effects of weight reduction on neutrophil phagocytic activity and oxidative burst activity in female judoists - Suzuki, M.; Nakaji, S.; Umeda, T.; Shimoyama, T.; Mochida, N.; Kojima, A.; Mashiko, T.; Sugawara, K. (Luminescence, 2003)
This study investigated the effects of short-term weight reduction on neutrophil functions in female judoists. Sixteen actively competing female judoists were divided into two groups. Eight who required weight reduction were defined as the weight reduction group, and the remaining eight were used as the control. Blood samples were taken before, immediately after and 8 days after the match. Phagocytic activity and oxidative burst activity of neutrophils were measured by flow cytometry. In the weight reduction group, the phagocytic activity per cell decreased significantly at the end of weight reduction compared with the control group. The rate of neutrophils producing reactive oxygen species and the oxidative burst activity per cell increased significantly at the end of weight reduction in both the control and the weight reduction groups. We concluded that weight reduction, consisting of both intense exercise and energy restriction, might possibly cause both an increase in oxidative burst activity and decrease in neutrophil phagocytic activity in female judoists. However, although exercise increased oxidative burst activity, it did not affect neutrophil phagocytic activity alone. Therefore, to avoid this problem, female judoists are recommended to keep their weight within those limits determined by their class, and which can be reduced by exercise.